2004
DOI: 10.1901/jaba.2004.37-535
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Behavioral Skills Training on Staff Implementation of Discrete‐trial Teaching

Abstract: A behavioral skills training package was used to train 3 teachers to correctly implement discrete-trial teaching. The mean baseline proportion of possible correct teaching responses for Teachers 1, 2, and 3 increased from 43%, 49%, and 43%, respectively, during baseline to 97%, 98%, and 99%, respectively, following training. These data indicate that the training package consisting of instructions, feedback, rehearsal, and modeling produced rapid and large improvements in the teachers' implementation of discret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
202
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 319 publications
(226 citation statements)
references
References 5 publications
14
202
0
10
Order By: Relevance
“…Following exposure to the instructional package, all participants demonstrated mastery performance of the attention, play, and demand functional analysis conditions. Similar results have been demonstrated when using BST to teach special education teachers the skills required for discrete-trial teaching (Sarokoff and Sturmey 2004). Behavioral skills training included instruction with written descriptions, modeling, rehearsal, and feedback.…”
Section: Verbal Behavior Milestones Assessment and Placement Programsupporting
confidence: 65%
See 1 more Smart Citation
“…Following exposure to the instructional package, all participants demonstrated mastery performance of the attention, play, and demand functional analysis conditions. Similar results have been demonstrated when using BST to teach special education teachers the skills required for discrete-trial teaching (Sarokoff and Sturmey 2004). Behavioral skills training included instruction with written descriptions, modeling, rehearsal, and feedback.…”
Section: Verbal Behavior Milestones Assessment and Placement Programsupporting
confidence: 65%
“…Alternatively, if written instructions are not sufficient in teaching professionals to administer the assessment, behavioral skills training (BST; Miltenberger 2008) may be an effective instructional method. BST consists of four components as follows: instructions, modeling, rehearsal, and feedback, and has repeatedly been demonstrated as an effective method for teaching a variety of clinical skills to paraprofessional staff and students (e.g., Rosales et al 2009;Sarokoff and Sturmey 2004). Iwata et al (2000) demonstrated the efficacy of a modified BST procedure when teaching undergraduates to implement functional analyses.…”
mentioning
confidence: 99%
“…An additional step was added that involved providing a rationale to the trainees (i.e., whom the participants would be training) regarding why the target skill would be trained. Providing a rationale is a recommended step when training staff (Fleming, Oliver, & Bolton, 1996;Willner et al, 1977) though it is not always specifically included in descriptions of BST (Miles & Wilder, 2009;Nigro-Bruzzi & Sturmey, 2010;Sarokoff & Sturmey, 2004). Also, one more step was added to clearly specify that the trainer should maintain a written record of each trainee's level of performance while practicing performing the skill being trained.…”
Section: Behavior Definitions and Observation Systemsmentioning
confidence: 99%
“…Behavioral skills training is an evidence-based approach for training human service personnel to implement behavior change and related procedures (Parsons, Rollyson, & Reid, 2012). Numerous work skills have been trained to staff in the human services through BST including how to teach consumers with disabilities (Sarokoff & Sturmey, 2004) and implement procedures to reduce problem behavior (Miles & Wilder, 2009). The significance of behavior analysts being skilled in BST is highlighted by demonstrations that without such skills, staff training is not likely to be consistently effective even if the staff trainer (e.g., behavior analyst) is skilled in implementing the behavior-change procedure that is being trained to staff (McGimsey, Greene, & Lutzker, 1995;Parsons & Reid, 1995).…”
mentioning
confidence: 99%
“…Behavior analysts have taught caregivers to implement DTT using behavioral skills training (BST). For example, Sarakoff and Sturmey (2004) used BST to teach three special education teachers how to implement DTT. The results showed that each of the teachers' implementation improved after training involving instructions, review of baseline data, modeling, rehearsal, and feedback.…”
mentioning
confidence: 99%